ANALISIS STRATEGI PELAYANAN DALAM MENINGKATKAN MINAT KONSUMEN DI TAMAN SARI ROYAL HERITAGE SPA - Teti Kuswati; Yessica Putri Rahmawati (Jurnal Socia Akademika, 2023)
This study aims to determine service strategies, roles and functions in increasing consumer interest in Taman Sari Royal Heritage Spa Yogyakarta. Type of descriptive qualitative research, data collection using interview, observation, and documentation techniques. The subject in this study is the Operations Manager. At the same time, the object is the service strategy at Taman Sari Royal Heritage Spa Yogyakarta to increase consumer interest. The results showed that Service strategies used at Taman Sari Royal Heritage Spa in increasing consumers include proof of physical and non-physical services, employee reliability in serving consumers, service guarantees, employee empathy, responsiveness, and prioritizing customer satisfaction. The role and function of service in increasing consumer interest are the function of service, function of communication, function of judgment, function of economics, and as function of competition. The role of service can attract consumers and increase market share, thereby establishing a good relationship between the company and consumers